Vocabulary learning strategies and the effects of game-based techniques on the lexical repertoire of young ESL learners - Kanthimathi Letchumanan, (2012)
Vocabulary is fundamental to communication, and mastering words is important in learning any language. Effective communication is usually judged by vocabulary ability. Most people who have learned a language are aware of how insufficient vocabulary can retard their communication. This study aimed to address the gap in studies on the effectiveness of using vocabulary games to enhance vocabulary among ESL learners in a selected secondary school. The objectives of the study were to investigate the types of vocabulary learning strategies learners have used prior to the study, to investigate which mode of vocabulary game is preferred by the learners, to examine the learners’ lexical frequency profile (LFP) in written essays and to investigate if ESL learners are able to use lexis from the vocabulary games to result in an improvement in vocabulary knowledge. The study employed a mixed-method research design to incorporate quantitative and qualitative data collection and analysis. The counterbalanced design was used to compare the effects of two modes of vocabulary games. In the study, two intact groups formed the experimental groups and underwent a vocabulary game treatment for fourteen weeks, playing computer and paper-based games at different stages. In the first stage, prior to the game treatment, the respondents wrote an essay each, and sat the Productive Vocabulary Levels Test (PVLT). The essays were processed using the VocabProfile, that categorized the words produced by learners in their essays into four levels of word frequency: 1000 word-level, 2000 word-level, Academic Word List (AWL) and Not-in-the-list (NIL) word-level. The VocabProfile results determine the LFP of the essays written by the learners. The PVLT that measured the learners’ vocabulary depth, were manually marked and scores was obtained. In the second stage of the experiment, the vocabulary game treatment was conducted for seven weeks. Group 1 played the computer-based games and group 2 paper-based games. Post- treatment Test 1 was conducted where both groups wrote parallel essays and sat the PVLT. In the third stage of the experiment, both the experimental groups switched treatments, and continued to play games for another seven weeks and participated in Post-treatment Test 2. They wrote another parallel essay and sat the PVLT. The respondents also answered a questionnaire and participated in an interview. The results revealed that the respondents preferred computer-based games to paper-based games. Both the experimental groups have improved in the vocabulary depth of the 2000 word-level after playing the vocabulary games which was shown from their PVLT results. The data analysis also showed that the respondents’ usage of vocabulary at the 2000 word-level measured through mean scores in their LFP had also increased although it was not statistically significant. The study suggests that the use of vocabulary games could be an effective technique for vocabulary learning among ESL learners. In other words, by gamifying vocabulary learning, even shy and slow learners would engage and participate in the language classroom because vocabulary learning becomes interesting, enjoyable and fun. This idea of gamifying vocabulary learning is an important contribution of the study to the research field.